Intervention Of Infrared (Ir) And Passive Exercise On Pain Reduction In Patients With Shoulder Pain - Dio Septiyan Helmi; Anggun Permata Sari; Anggi Yusriana; Rara Putri Maliza (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2025)
Shoulder pain is a musculoskeletal disorder that can cause discomfort, limited upper body movement, and a reduced quality of life. Physical activities or sports that involve repetitive use of the upper extremities, such as badminton, volleyball, or weightlifting, often cause spasms or injuries to the shoulder muscles. Infrared (IR) therapy provides superficial heat that can increase vasodilation, improve blood circulation, and reduce muscle spasms, while passive exercises aim to maintain or increase ROM and muscle strength. However, research on the combined effects of IR and passive exercises on shoulder pain is still limited. This study is an experimental study (quasi-experimental) with a one-group pretest-posttest design involving 10 respondents with shoulder pain. The intervention was carried out for 16 treatments with a frequency of 3-4 times a week. IR was administered at a distance of ± 30 cm from the skin surface in the shoulder area for 10-20 minutes per session. Pain levels were measured using the VAS before and after the intervention. Data were analyzed using the paired sample t-test. The results showed a significant decrease in pain levels from 7.60 ± 1.50 to 1.80 ± 1.13 (p=0.000) with an average decrease of 5.80 and a very large effect size (Cohen's d = 4.4). The combination of IR and passive exercises was proven to be effective in reducing shoulder pain through improved blood circulation, muscle relaxation, and increased ROM. This combination therapy can be recommended as a simple, safe, and effective non-pharmacological physiotherapy intervention for patients with shoulder pain